Response of Latex Production At Various Times Application In Quick starter Clone Rubber Plant of Giving Stimulant Ethylene Peel of Banana Below the Tapping - tomi sandi gultom; charloq charloq (Jurnal Agroekoteknologi, 2017)
The experiment was conducted for six months, began in September 2015 to Februari 2016 in Sungei Putih Rubber Research Institute, Deli Serdang. Three-Stage Nested Design was applied with three replications. The first step was time application, i.e., a first application, a second application, the second step of clones treatment, i.e., IRR 118 clones, PB 260 clones and the third step was stimulants, i.e., without stimulants, stimulant extract 50 grams the peel of banana, stimulant extract 100 grams the peel of banana, stimulant extract 150 grams the peel of banana, stimulant extract 200 grams the peel of banana. Observed parameters was total solid contents. The results showed that first application was more bigger than the second application to produced the latex. PB 260 clones were clones that experienced the highest increase in producing due to the provision treatment of stimulants. Stimulant extract 100 gram the peel of banana is stimulant that tends to increase production latex higher than others.